Identification of microRNA expression profile related to lymph node status in women with early-stage grade 1–2 endometrial cancer - Canlorbe, Geoffroy; Wang, Zhe; Laas, Enora; Bendifallah, Sofiane; Castela, Mathieu; Lefevre, Marine; Chabbert-Buffet, Nathalie; Daraï, Emile; Aractingi, Selim; Méhats, Céline; Ballester, Marcos (Modern pathology, 2016)
Conventional methods used for histologic classification and grading of endometrial cancer (EC) are not sufficient to predict lymph node metastases. microRNA signatures have recently been related to EC pathologic characteristics or prognosis. The aim of this study was to evaluate whether microRNA profiles of grade 1–2 endometrioid adenocarcinomas can be related to nodal status and used as a tool to adapt surgical staging in early-stage EC. microRNA expression was assessed in nine formalin-fixed paraffin-embedded (FFPE) EC primary tumors with positive lymph node and in 27 FFPE EC primary tumors with negative lymph node, matched for grade, stage, and lymphovascular space involvement status. A microarray analysis showed that there was more than a twofold significant difference in the expression of 12 microRNAs between the two groups. A quantitative reverse transcriptase–PCR assay was used to confirm these results: the expression levels of five microRNAs (microRNA-34c-5p, -375, -184, -34c-3p, and -34b-5p) were significantly lower in the EC primary tumor with positive lymph node compared with those with negative lymph node. A minimal P -value approach revealed that women with a microRNA-375-fold change <0.30 were more likely to have positive lymph node ( n =8; 53.3%) compared with those with a microRNA-375-fold change >0.30 ( n =1; 4.8%), P =0.001. Furthermore, women with a microRNA 184-fold change <0.30 were more likely to have positive lymph node ( n =6; 60.0%) compared with those with a microRNA 184-fold change >0.30 ( n =3; 11.5%), P =0.006. This is the first study investigating the relative expression of mature microRNA genes in early-stage grade 1–2 EC primary tumors according to the nodal status. This microRNA expression profile provides a potential basis for further study of the microRNA function in EC and could be used as a diagnostic tool for nodal status.